The tragedy of the commodity is not inevitable: Indigenous resistance prevents high-value fisheries collapse in the Pacific islands. (March 2022) - Ferguson, Caroline E.; Bennett, Nathan J.; Kostka, William; Richmond, Robert H.; Singeo, Ann
Highlights: The emergence of export markets for high-value fisheries tends to lead to collapse. We examine three case studies of resistance to the high-value seafood trade. Despite short-term financial incentives, fishing communities rejected export markets. Communities asserted Indigenous values and governance in the face of capitalist incursion. Communities recommonized their fisheries and prevented collapse. Abstract: The emergence of export markets for high-value seafood products tends to produce a predictable pattern of serial depletion of resources and social disruption in coastal communities, a phenomenon described as 'the tragedy of the commodity'. The sea cucumber trade epitomizes these challenges, with cases of rapid growth followed by fishery collapse documented across the Indo-Pacific and the majority of assessed stocks worldwide overexploited. Is this 'boom-bust' sequence inevitable? We examine three cases of resistance to the sea cucumber trade from Palau, Pohnpei, and Yap. Despite the overwhelming short-term financial incentives to export, fishers, youth, elected and traditional leaders, and civil society organizations coordinated to ban the trade at its peak, using public protest, court battles, and customary and statutory law. We show that, like the tragedy of the commons, Indigenous peoples and local communities can organize to resist the tragedy of the commodity. They do so by asserting Indigenous values, rights, and institutions, recommonizing the resource and preventing fisheries collapse. These cases challenge the inevitability of the tragedy of the commodity and the narrative of poor fishers as vulnerable and disempowered.